Alstorisine A, a nor-monoterpenoid indole alkaloid from cecidogenous leaves of Alstonia scholaris. Issue 16 (20th April 2016) - Chen, Ying-Ying; Yang, Jing; Yang, Xing-Wei; Khan, Afsar; Liu, Lu; Wang, Bei; Zhao, Yun-Li; Liu, Ya-Ping; Ding, Zhong-Tao; Luo, Xiao-Dong
Graphical abstract: Highlights: A nor -monoterpenoid indole alkaloid was isolated from A. scholaris . A plausible biogenesis of the isolated alkaloid was postulated. Alstorisine A appeared equally in galls and normal part of cecidogenous leaves. It was present at 3 μg/g as indicated by LC–MS quantitative analysis. Abstract: Alstorisine A (1 ), a novel nor -monoterpenoid indole alkaloid with 6/5/6/6 fused-ring system, regarded as a key intermediate from melodinine E to mersicarpine, was isolated from the cecidogenous leaves of Alstonia scholaris . Its structure was identified on the basis of extensive spectroscopic analysis and the comparison of experimental and calculated ECDs. A plausible biogenesis was also postulated.